Developments in research data management in academic libraries: Towards an understanding of research data service maturity. (25th March 2017) - Cox, Andrew M.; Kennan, Mary Anne; Lyon, Liz; Pinfield, Stephen
Abstract : This article reports an international study of research data management (RDM) activities, services, and capabilities in higher education libraries. It presents the results of a survey covering higher education libraries in Australia, Canada, Germany, Ireland, the Netherlands, New Zealand, and the UK. The results indicate that libraries have provided leadership in RDM, particularly in advocacy and policy development. Service development is still limited, focused especially on advisory and consultancy services (such as data management planning support and data‐related training), rather than technical services (such as provision of a data catalog, and curation of active data). Data curation skills development is underway in libraries, but skills and capabilities are not consistently in place and remain a concern. Other major challenges include resourcing, working with other support services, and achieving "buy in" from researchers and senior managers. Results are compared with previous studies in order to assess trends and relative maturity levels. The range of RDM activities explored in this study are positioned on a "landscape maturity model, " which reflects current and planned research data services and practice in academic libraries, representing a "snapshot" of current developments and a baseline for future research.